Corporate Social Responsibility and Firm Value of Mining Companies in Indonesia - Era, Teguh; Basri, Mahrani (Invoice : Jurnal Ilmu Akuntansi, 2022)
This study aims to prove the effect of company performance, Corporate Social Responsibility and profitability partially on the value of mining companies on the Indonesia Stock Exchange for the 2016-2020 period. To prove the effect of company performance, Corporate Social Responsibility  and profitability simultaneously on the value of mining companies on the Indonesia Stock Exchange for the 2016-2020 period. The population used in this study are mining companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020 which have complete and published financial reports. The type of data used in this research is secondary data. Purposive Sampling Sampling Technique,. Collecting data in this study using the method of documentation. The analysis technique used is multiple linear regression with a significance level of 5%. The results show that partially financial performance, Corporate Social Responsibility and profitability have a positive and significant effect on the value of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. Simultaneously financial performance, Corporate Social Responsibility and profitability have a significant effect on the value of mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period.Keywords: Financial Performance, Corporate Social Responsibility, Profitability and Firm Value